Spontaneous Pattern Formation in a Polariton Condensate - Liew, Timothy Chi Hin (2017)
Exciton-polariton condensation can be regarded as a self-organization phenomenon, where phase ordering is established among particles in the system. In such condensed systems, further ordering can occur in the particle density distribution, under particular experimental conditions. In this work we report on spontaneous pattern formation in a polariton condensate under nonresonant optical pumping. The slightly elliptical ring-shaped excitation laser that we employ forces condensation to occur into a single-energy state with periodic boundary conditions, giving rise to a multilobe standing-wave patterned state.